PENGEMBANGAN KARIER PADA PEREMPUAN (Studi Fenomenologi pada Karyawan Perempuan PT. Semen Indonesia) - Lumingkewas, Inryani Greysita; Mas’ud, Fuad (Diponegoro Journal of Management, 2017)
Woman and man must have equality labor rights, including in their career development. Every employee has role to make the organization grow. This study address to see the implementation of the career development of the company for its employees especially those for women.The purpose of this study was to analyze how participants perceived career development provided by the company. How they feel and experience in using or opportunity in career development. Besides, the research uncover the drivers and obstacles they face in developing their career. The method used in this study is qualitative method with phenomenological study approach. Data collected by interview, observation and documentation in certain periods.The results showed in general career development is done without differentiating women and men. Women can balance their role in society, family and career even though the job description is not too small.